Synchronizing phasor measurement and STATCOM controller in power system stability enhancement - Debasish Mondal (Institute of Advanced Engineering and Science, 2021)
The objective of this paper is to present the concepts of synchronizing phasor measurement (SPM) and its strategic application in addition with a STATCOM controller for augmentation of dynamic stability in a multimachine power network. The bus voltages of the power network under consideration are estimated in the form of digital signal by a synchronizing phasor measurement unit (SPMU). The output of the PMU is then applied to a fixed structure PI type lead-lag digital STATCOM controller in order to study the performance of this discrete-time digital control in comparison to its analog counterpart for the present control problem. The parameters of the analog controller are first tuned with a popular soft computation technique, particle swarm optimization (PSO) and later this controller is converted to digital one for simulation with sampled data outputs received from SPMU. The validation and effectiveness of the design of the proposed control scheme is illustrated through time domain simulation of a proposed 3- machine, 9-bus test power system. The simulation results of the machine speed deviation response established that the SPM based digital control system is more effectual and resulting better performance than the continuous-time analog control system in power system stability improvement.